The prerequisites for hardware and software support in the digitalization of sports - Ermakov A.V.; Skarzhinskaya E.N.; Beresneva V.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to substantiation of requirements for the development of sports APC in the context of phygitalization. Results of the study and discussion. A retrospective examination of scholarly articles and empirical investigations in the realm of the development and implementation of sports APC. The examination of the four stages of the evolution of the sports agro-industrial complex in the context of digitalization has led us to identify the following prerequisites: The APC must encompass at least one stage of sports training, providing all the necessary tools for coaches and athletes in competitive activities. It should not only evaluate individual parameters but also a system of measured parameters. The coach should be able to combine, create, and modify existing programs. The system should allow for the collection of both raw data and data that has been processed using artificial intelligence technologies, at a selected level of generalization, while maintaining the declared accuracy parameters. It should also enable seamless interaction with data, ensuring that no qualitative or quantitative losses occur during active sports activities. Additionally, it should be immune to theft or malicious use, thanks to the use of wireless and cloud technologies. Collaborate with a wide range of digital offerings and engage with the community.